Men go to battle [videorecording (DVD)] - Treitz, Zachary; Sheil, Kate Lyn; Sheil, Kate Lyn; Morton, Tim; Maloney, David (Actor) (Film Movement series., 2016)
Bracing for another winter on their struggling farm in rural Kentucky, brothers Henry and Francis Mellon have become suffocatingly close. Francis' practical jokes become more and more aggressive until the night he accidentally injures Henry in a drunken fight. After humiliating himself in front of a daughter of the town's preeminent family, Henry disappears in the night. Months later, Francis learns that Henry has joined the Union army.